Modelling of CO2 Laser Materials Processing by Networked Neuro-Dimension Fuzzy Intelligent System - Sivarao, Subramonian; S., Thiru; Jusoff, Kamaruzzaman; Azizah, Shaaban; Mariana, Yusoff; Jano, Zanariah; Yuhazri, Yaakob; HASOLOAN , HAERY IAN PIETER; Abu Bakar, Mohd Hadzley; Raja, Izamshah; Hussein, Nur Izan Syahriah; Mohd Amran, Md Ali; et al. (INSInet Publications, 2013)
The usage of non-contact machine tools in metal cutting industries is increasing exponentially in recent times due to the advent of super hard work materials. The fiercely competitive manufacturing industries find the traditional trial-and-error method, not only challenging and time consuming but also economically nonviable in acquiring superior quality of end products produced from such materials. This paper presents a more accurate prediction method for surface roughness values by using Networked Fuzzy Intelligent System (N-FIS) in combination with the commercial software tools, Matlab and Neuro-Dimension Network. Experiments were conducted on manganese molybdenum pressure vessel plates to validate the robustness of the developed model in forecasting the surface roughness values. The predicted results were found to be reasonably accurate with an error percentage well below 10% for almost all runs at the prediction stage. On the other hand, the experimental validation results for selected critical runs were found to be extremely promising with results of an accuracy of more than 90%. It was concluded that the setting of proper network algorithm and rules, can actually help the industry to perform laser machining better by saving huge waste materials by employing the approach presented in this paper as compared to the traditional trial-and-error method.